Making Curriculum Visible Through a Multi-Dimensional, Interactive Curriculum Map, MyCourseMap - Tee, Lisa; Serrano Santos, Jose; Seaman, Kristen; Sim, Tin; Bedford, Simon; Tee, Lai (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education, 2021)
Universities often find it challenging to provide students with an effective and holistic view of their program and its disciplinary outcomes. To provide a transparent visualisation of the curriculum, a multi-dimensional and interactive curriculum map tool, MyCourseMap, was developed. This study utilises mixed methods to explore how prepared Australian universities are in providing explicit information on the curriculum to staff and students. Staff and students reported a lack of awareness of course learning outcomes and graduate attributes adding to the issue of students not fully comprehending how their degree is aligned with employment expectations. MyCourseMap served to help resolve these coherence and visualisation issues.